2010
DOI: 10.1075/ijcl.15.1.01xia
|View full text |Cite
|
Sign up to set email alerts
|

How different is translated Chinese from native Chinese?

Abstract: Corpus-based translation studies focus on translation as a product by comparing comparable corpora of translational and non-translational texts. A number of distinctive features of translational English in relation to native English have been uncovered. Nevertheless, research of this area has so far been confined largely to translational English translated from closely related European languages. If the features of translational language that have been reported on the basis of translated English are to be gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 14 publications
2
38
0
2
Order By: Relevance
“…We also tagged these words with parts of speech in order to retrieve all the country names. The software we used is ICTCLAS, the most widely employed Chinese POS tagging and word segmenting software (Xiao, 2010), which covers the tagging of place names. To ensure segmentation and POS tagging are correct, manual proofreading by native Chinese speakers was also carried out.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…We also tagged these words with parts of speech in order to retrieve all the country names. The software we used is ICTCLAS, the most widely employed Chinese POS tagging and word segmenting software (Xiao, 2010), which covers the tagging of place names. To ensure segmentation and POS tagging are correct, manual proofreading by native Chinese speakers was also carried out.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…It is vital since it is still unknown what factors (and to what an extent) impact basic stylometric indicators. Also, more quantitative research on translation universals in Polish (in line with studies by Scarpa 2006, Corpas Pastor et al 2008, Xiao 2010, including examination of other T-and S-universals (i.e. explicitation, simplification, normalization, sanitization and levelling out) should be conducted in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Such a decision is dictated by the results of a number of quantitative and qualitative studies of TUs (e.g. Corpas Pastor et al 2008, Scarpa 2006, Xiao 2010) which revealed that a direction of translation, or language pairs involved in the translation process, may impact basic stylometric indicators.…”
Section: Introductionmentioning
confidence: 99%
“…4-grams (see Biber et al 2004), and without giving any special attention to a particular type of 3-gram from the outset (e.g. Baker 2004, Xiao 2010, 2011.…”
Section: Introductionmentioning
confidence: 99%